Abundance and diversity of edaphic mites (Arachnida, Acari) under different forest management systems in Indonesia - Muhammad Ihsan; Retno Dyah Puspitarini; Aminudin Afandhi; Ito Fernando (Society for Indonesian Biodiversity, 2021)
Abstract. Ihsan M, Puspitarini RD, Afandhi A, Fernando I. 2021. Abundance and diversity of edaphic mites (Arachnida, Acari) under different forest management systems in Indonesia. Biodiversitas 22: 3685-3692. Edaphic mites play crucial roles in maintaining ecosystem services that are essential to human needs. However, the conversion of natural habitats followed by agricultural intensification may adversely affect edaphic mites. The objective of this study was to investigate the influence of different management systems on edaphic mite abundance, richness, and diversity in tropical rain forests in Indonesia. There were five forest management systems, which were as follows: secondary forest, production forest (pine monoculture), and three agroforestry systems (pine + coffee, mahogany + coffee, and mahogany + new cocoyam). We established a transect containing five research plots for each forest management system. Litter and soil from each plot were collected from December to March 2021. Temperature, relative humidity, and pH of litter and soil, as well as litter thickness, were measured. We found that edaphic mite abundance, richness, and diversity in the secondary forest were similar to managed forests. However, the aforementioned variables were significantly higher in “pine” systems than in “mahogany” systems. Our analysis evidenced positive correlations between litter thickness and edaphic mite abundance, richness, and diversity. Our findings may assist in selecting the appropriate forest management systems to rationalize the conversion of secondary forests to production forests and agroforestry.